Design and evaluation of children’s education interactive learning system based on human computer interaction technology - Mengru Li; Yang Lv; Yongming Pu; Min Wu (Scientific Reports)
Abstract This study aims to develop and evaluate an interactive learning system for children. Through mixed-method research, combined with quantitative and qualitative data analysis, this study provides a comprehensive evaluation of the educational effectiveness of the system. The study involves children in grades 1–6, and data on learning effectiveness before and after using the system are collected through pre-experiments and formal experiments. The results of the quantitative analysis show that after using the system, the average improvement rates for students in grades 1–3 and 4–6 are 24.6% and 22.2% in mathematics and 28.1% and 26.8% in science. The average response time of the system is 1.77 s, with the longest response time being 3.1 s. User satisfaction reaches 94%, and the error rate is 0.2%. These results demonstrate that the developed learning system significantly impacts children’s learning effectiveness and optimizing user experience.